Flare pathways for inflammatory bowel disease. (2nd July 2019) - Barrett, Kevin
Abstract : The prevalence of inflammatory bowel disease (IBD) in the UK population is rising; yet 52% of GPs say they are less than confident in managing flares. A new set of standards for IBD management in primary care has been launched to help address the problem